Antibiotic prescriptions for oral diseases in India: evidence from national prescription data - Manu Raj Mathur; Deepti Nagrath; Vijay Kumar Mishra; Rebecca Harris; Syed Saif Saeed; Sakthivel Selvaraj; Aashna Mehta; Habib Hasan Farooqui (BMC, 2023)
Abstract Introduction The key objective of this research was to describe the prescription rate of various antibiotics for dental problems in India and to study the relevance of the prescriptions by analysing antibiotic types associated with different dental diagnoses, using a large-scale nationally representative dataset. Methods We used a 12-month period (May 2015 to April 2016) medical audit dataset from IQVIA (formerly IMS Health). We coded the dental diagnosis provided in the medical audit data to the International Statistical Classification of Diseases and Related Health Problems (ICD-11) and the prescribed antibiotics for the diagnosis to the Anatomic Therapeutic Chemical (ATC) -2020 classification of the World Health Organization. The primary outcome measure was the medicine prescription rate per 1,000 persons per year (PRPY1000). Results Our main findings were-403 prescriptions per 1,000 persons per year in the year 2015 -2016 for all dental ailments. Across all ATC level 1 classification, 'Diseases of hard tissues' made up the majority of the prescriptions. 'Beta-lactam', 'Penicillin,' and 'Cephalosporins' were the most commonly prescribed antibiotics for dental diagnoses followed by 'Macrolides' and 'Quinolones'. 'Dental caries', 'Discoloration of tooth', and 'Toothache' were the most common reasons for 'Beta-Lactams' and 'Penicillin' prescriptions. Conclusion To conclude our study reports first ever country (India) level estimates of antibiotic prescription by antibiotic classes, age groups, and ICD-11 classification for dental ailments.